Mapping the potential human health implications of groundwater pollution in southern Sri Lanka - Rajasooriyar, L.D.; Boelee, E.; Prado, M.C.C.M.; Hiscock, K.M. (Elsevier, 2013)
In southern Sri Lanka, irrigation in uences the concentrations of faecal bacteria and inorganic toxic contaminants in groundwater. We develop a groundwater vulnerability map describing the potential human health implications of harmful constituents in the Uda Walawe Basin, by overlaying geological and land use data with information describing the irrigation system, the oxygen iso tope composition of water bodies, and the concentrations of selected contaminants. Given the limited data available, we exam ine the spatial distribution of harmful constituents and the poten tial human health risks. Fluoride poisoning from groundwater is the greatest health threat in our study area, where uoride concen trations ranging from 0.1 to 9.2 mg/L are associated with a geologic origin. Arsenic occurs in high concentrations, up to 0.4 mg/L, in areas with low recharge, although the source of arsenic is not clear. Nitrate concentrations are low, ranging from 0.4 to 23mg/L, despite high fertilizer inputs, except in areas with low recharge and non-favourable reducing conditions, where concentrations
Keywords: Fluoride; Arsenic; Nitrate; Irrigation; Crystalline rock aquifers; Vulnerability map